Japan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper for Japan illustrates the impact of fiscal and structural reforms on the Japanese and world economies. Japan faces a sizable fiscal deficit, against a backdrop of weak trend growth and growing imbalances in the world economy. Moreover, upward pressure on health care and social security spending owing to an aging population will add significantly to strains on public resources in the near future. The Japanese government is taking a range of measures aimed at raising productivity growth and stabilizing the public debt in relation to GDP over the medium term.